The cost of total hip arthroplasty: compare the hospitalization costs of national centralized procurement and national volume-based procurement - Fan, Yongyong; Xu, Qiang; Jin, Gang; Jiang, Lingjun; Wang, Chenglong (Frontiers in Public Health, 2024)
Background: With the increasing demand for joint replacement surgery in China, the government has successively issued the policies of national centralized procurement (NCP) and national volume-based procurement (NVBP) of artificial joints. The purpose of this study is to evaluate the impact of NCP and NVBP policies on hospitalization cost, rehospitalization and reoperation rate of total hip arthroplasty (THA). Methods: In total, 347 patients who underwent THA from January 2019 to September 2022 were retrospectively analyzed. According to the implementation of NCP and NVBP, patients were divided into three groups: control group (n = 147), NCP group (n = 130), and NVBP group (n = 70). Patient-level data on the total hospitalization costs, rehospitalization rate, THA reoperation rate and inpatient component costs were collected before and after the implementation of the policies and Consumer Price Index was used to standardize the cost. Results: After the implementation of NCP and NVBP, the total cost of hospitalization decreased by $817.41 and $3950.60 (p<0.01), respectively. The implantation costs decreased from $5264.29 to $4185.53 and then rapidly to $1143.49 (p < 0.01), contributing to increased total cost savings. However, the cost of surgery and rehabilitation increased after NCP and NVBP implementation (p < 0.01). The proportion of implants decreased from 66.76% to 59.22% and then to 29.07%, whereas that of drugs increased from 7.98% to 10.11% and then to 12.06%. The proportion of operating expenses rose from 4.86% to 8.01% and then to 18.47%. Univariate linear regression analysis showed that hospital stay, NCP and NVBP were correlated with total hospitalization cost (p < 0.01). Multivariate analysis showed that hospital stay, NCP and NVBP were independent predictors of total hospitalization cost (p<0.01). Conclusions: In this study, hospital stay, NCP, and NVBP were independent predictors of total inpatient costs. After the implementation of NVBP policy, the cost of implants and hospitalization has decreased significantly, and the technical labor value of medical staff has increased, but a multifaceted method is still needed to solve the problem of increasing costs of other consumables. Limitations of the study suggest the need for further and more comprehensive evaluation in the future.